PENGARUH ETHICAL LEADERSHIP TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR : PERAN MEDIASI MEMBER EXCHANGE - Ebtariadi; Adi Rahmat; Fahmi Oemar (Indragiri Research Center (ingreat), 2025)
This research is also motivated by the research gap of previous research which discusses leadership style more broadly and the lack of research in Indonesian that discusses ethical leadership and its relationship to organizational citizenship behavior. In previous studies, leader member exchange has not been found as a mediation mechanism that discusses the influence of ethical leadership on organizational citizenship behavior. This research is a type of quantitative descriptive research with a causal research design with a population of state civil servants at the Regional Finance and Asset Agency of Indragiri Hilir Regency with a population of 51 state civil servants and a sample using the census method. Data collection techniques using questionnaires and distribution using google forms. The data analysis tool in this study is Structural Equation Modeling (SEM) processed using SmartPLS 32.9 for data processing. From the findings of this study, it was found that ethical leadership has a positive and insignificant effect on organizational citizenship behavior, ethical leadership has a positive and significant effect on leader member exchange, leader member exchange has a positive and significant effect on organizational performance and ethical leadership has a positive and significant effect on organizational performance through leader member exchange.